The effectiveness of service quality of mobile telecommunication service provider in Miri, Sarawak / Yussof Bujang - Bujang, Yussof (2007)
The purpose ofthis research is to measure the Level of Service Quality of Mobile Telecommunication Service Provider in Miri,Sarawak.Objectives ofthis study is to rank the Service Quality dimension.Information gather from this study will benefits and help the Mobile Telecommunication Service Provider to improve further in providing Service Quality to their client.This study include various sector like Petronas Carigali Sdn Bhd,Sarawak Shell Berhad, Private Firm banking sector.Data was collected from 100 employee from Various Sector The findings indicates that there is no significant differences between the Mobile Telecommunication Service provider in Miri interms the Level ofsevice quality.However in this study,the researcher found that most respondents are worry about their personal data being distributed among the unauthorised . From the feedback obtained ,the organization can further find a way on how to improve the Level of Mobile Telecommunication Service provider in Miri.